Pengaruh Akuntabilitas Dana Desa dan Keterbukaan Informasi Terhadap Partisipasi Masyarakat Kecamatan Sukanagara - Wiliandani, Alit (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
This study aims to evaluate the impact of village fund accountability and public information transparency on community participation in Sukanegara District. Using a quantitative approach and an explanatory research design, the study involved 170 respondents selected through purposive sampling techniques. Data were analyzed using the Structural Equation Modeling method based on Partial Least Square (SEM-PLS). The results indicate that village fund accountability has a positive and significant effect on community participation. This shows that the better the village government's accountability in managing the budget, the higher the level of citizens’ participation in development. In addition, transparency of public information also has a proven positive and significant effect on community participation. Easy access to information about village programs and budgets is an important factor that encourages residents to take part in monitoring and implementing activities. Overall, these two variables are able to explain 88.4% of the variation in community participation, with a strong level of predictive validity for the model. These findings emphasize the importance of strengthening transparent and accountable village governance to create a harmonious partnership between the government and the community for sustainable village development.